Mental health and BMI in children and adolescents during one year in obesity treatment - Katrine Decker Iversen; Trine Pagh Pedersen; Mette Rasmussen; Maj-Britt Lundsgaard Hansen; Birgitte Højgaard Roikjer; Grete Teilmann (BMC, 2024)
Abstract Background Mental health plays a major role in children and adolescents with obesity. The aim of this study was (1) to compare mental health in children with obesity with the background population and (2) to investigate if mental health changed during one year in an obesity treatment program. Methods Data on self-reported mental health was collected in 107 children and adolescents (mean age 13.2 years) with obesity at first visit in an obesity treatment program and at one year follow-up (n = 47). Mental health was assessed by eight questions from the Danish Health Behaviour in School-aged Children (HBSC) questionnaire: (1) self-rated health (2) life satisfaction (3) feeling low (4) body-image (5) loneliness (6) self-esteem (7) self-efficacy and (8) social competence. Data was compared to a reference population based on HBSC data. BMI-SDS was based on Danish reference values. Results Children and adolescents with obesity had significantly higher odds of reporting negative body image and feeling low and lower odds of reporting high self-rated health and high self-esteem compared to a reference population. There was no difference between the groups regarding life-satisfaction, social competence, self-efficacy or feeling lonely. There were no significant changes in mental health from first visit to one-year follow-up. Conclusion Our findings highlight the mental health difficulties in children and adolescents with obesity, and the importance of addressing these issues in obesity treatment. The results also indicate that children with obesity have psychosocial resources that should be exploited in treatment protocols.